Analysis of the Critical Chain Project Management (CCPM) method, BIM 3D, and Last Planner System on Contractor Performance and High Rise Building Project Duration - Ariza, Franrizka; Suroso, Agus; Amin, Mawardi (Green Publisher Indonesia, 2025)
This study examines the effectiveness of project implementation by evaluating the impact of Critical Chain Project Management (CCPM), Building Information Modeling (BIM), and the Last Planner System (LPS) on contractor performance and the timeliness of high-rise building projects. Effective scheduling is crucial in construction, as it aims to minimize process time, waiting time, and inventory levels while ensuring the efficient use of resources. The research is motivated by the frequent delays observed in high-rise building projects during the construction phase. The study employed SPSS to analyze data, revealing that the combined use of CCPM, BIM, and LPS significantly improves contractor performance and project implementation time, with a p-value of 0.000, indicating a strong influence. Specifically, the application of the CCPM method reduced the project timeline from 314 days to 235 days, achieving a 33.4% optimization in time. Additionally, the use of BIM 3D modeling facilitated rapid visualization of building progress across different floors, while the implementation of the LPS method improved the Percent Plan Completed (PPC) value from below 70% to 89.49%. The findings suggest that employing these methods enhances the accuracy of project timelines and reduces delays, offering valuable insights into improving construction project management practices.